Đặc điểm cổ sinh thái và phân bố cảu hóa thạch răng nón, vỏ nón trogn các trầm tích D3-C1 ở một số vùng thuộc bắc bộ. - Phương, Tạ Hòa; Thuận, Nguyễn Công (VNU Journal of Science: Natural Sciences and Technology, 2004)
In Bac Bo region the Da-Cj sediments, containing pelagic fossil groups Conodonts and Tentaculites, belong to deep facies type and are mainly of calcareous, silicic and terrigen-silicic composition. Based upon the features of sediments and their distribution, one can find that they mainly were formed in the deep and narrow troughs, which are possibly of tectonic origin and located in the carbonate platform areas. Among them the next typical rock types can be distinguished: 1) Lens- and nodul-shaped, grey or multicoloured, griotte clayey limestones (the Toe Tat Formation in the Ha Lang, Dong Van areas; the Suoi Nho Formation in the Northwestern of Bac Bo 2) Striped limestones (the uppermost part of the Trang Kenh Formation in the Kinh Mon area). 3) Cherts and shales (the Bang Ca Formation in the Ha Lang area, the Phuc Son Formation in the Ham Rong area); 4) Medium- to thin-bedded limestones, clayey limestones, siliceous limestones (the uppermost part of the Si Phai Formation in the Dong Van area, the lowemost part of the Pho Han Formation in the Cat Ba isle; 5) Thin-bedded or banded black limestones, siliceous limestones (the intermediate part of Pho Han Formation in the Cat Ba isle.